A Review: Metal Filled Thermoplastic Composites. Issue 10 (3rd July 2021) - Zaaba, Nor Fasihah; Ismail, Hanafi; Saeed, Alaa Muhsin
ABSTRACT: In current years, metal-filled thermoplastic composites have gained increasing consideration due to their superior properties such as high fatigue and fire resistance, high impact damage, high corrosion resistance as well as low environmental degradation. The combination of the favorable characteristics of metal and thermoplastic making them an ideal candidate in the various advanced application including automotive, aerospace, and electronic equipment. The final properties of metal-filled thermoplastic composites are influenced by few factors such as porosity, distribution, shape, and morphology of metal particles. This review article provides some important information. First, this article covers the information on structure and types of thermoplastic. There are three types of thermoplastics: standard thermoplastic, engineering thermoplastic, and high standard thermoplastics. Second, the periodic table of metals and nonmetals elements as well as their properties are covered. Third, properties of metal-filled thermoplastic composites as well as packing arrangement distribution of metal-filler particles in polymer matrix were discussed. Moreover, preparation, mechanical, thermal, and electrical properties as well as the application of metal-filled thermoplastic composites in various industries are covered in this article.